The Concept of Tawheed: Allah, Revelation, and al-Risalah as the Axiomatic Basis of Education - Nst, Anjar Mahmaudin; Alwizar, Alwizar; M. Yusuf, Kadar (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This research aims to examine the concept of monotheism and its relevance as an axiomatic basis in Islamic education. Through literature studies, this research explores various literature that discusses monotheism, revelation, and al-Risalah as the main foundation in the Islamic education system. The analysis method used is descriptive, by explaining and exploring the main ideas related to the topic being studied. The results of the study show that the concept of monotheism, which is rooted in the belief in the oneness of Allah, together with wahyu and al-Risalah, are fundamental and mutually reinforcing elements in shaping the direction and goals of Islamic education. The implementation of monotheistic values in the learning process is expected to be able to form a generation with strong character who is ready to contribute to the progress of the nation and religion.